2019
DOI: 10.3390/w11040697
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on a Hydraulic and Water-Quality Analysis Method for Determining Rechlorination Injection Points for a Water-Supply Network

Abstract: Water supply facilities are vulnerable to extreme weather events, such as droughts and floods. To establish a sustainable solution that resists accidents and disasters, a distributed system is required. To supply high-quality tap water using the existing water-supply network, rechlorination facilities must be installed to secure residual chlorine at the pipe end. In this study, a process is developed to determine the injection points and dosages of rechlorination using the latest pressure-driven analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was confirmed that a PDA-based solution tends to locate the injection points at an upstream divergence, whereas DDA-based solutions locate them at the end of a branched network. Similar to Yoo et al [2], Lee et al [5] highlighted the importance of a realistic network simulation (PDA) in performing WDS resilience studies that are mostly based on abnormal failure conditions (e.g., low pressure from a pipe break). In future studies, methodologies to minimize the risk originating from having multiple distributed rechlorination facilities (e.g., rechlorination ROB) could be developed to maintain the residual chlorine concentration, even under the failure of a single chlorine injection point.…”
Section: Hydraulic Parameter Monitoring For Wds Rapidity Improvementmentioning
confidence: 90%
See 4 more Smart Citations
“…It was confirmed that a PDA-based solution tends to locate the injection points at an upstream divergence, whereas DDA-based solutions locate them at the end of a branched network. Similar to Yoo et al [2], Lee et al [5] highlighted the importance of a realistic network simulation (PDA) in performing WDS resilience studies that are mostly based on abnormal failure conditions (e.g., low pressure from a pipe break). In future studies, methodologies to minimize the risk originating from having multiple distributed rechlorination facilities (e.g., rechlorination ROB) could be developed to maintain the residual chlorine concentration, even under the failure of a single chlorine injection point.…”
Section: Hydraulic Parameter Monitoring For Wds Rapidity Improvementmentioning
confidence: 90%
“…While category (3) included visualization methods to represent the system's criticality, category (2) summarized three papers to improve the capacity of WDS to supply customers' demands under earthquakes, a representative catastrophic failure event for resilience. Studies included in themes (4) and (5) proposed novel design methods and monitoring approaches for improving WDS resilience, respectively. The contributions of each study were described in the context of WDS resilience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations